New Interest Associations in a Neo‐Corporatist System: Adapting the Swiss Training System to the Service Economy. (8th December 2020) - Strebel, Alexandra; Emmenegger, Patrick; Graf, Lukas
Abstract: Collective skill formation systems need to adapt to economic change, most notably the expansion of the service economy. However, deeply anchored in the craft and industrial sectors, these systems rely on neo‐corporatist institutions to undergird firms' training provision, which are often missing in the service sector. We show that Switzerland's voluntaristic approach to interest intermediation provided the flexibility needed to extend vocational training to economic sectors without neo‐corporatist institutions. Yet, these adaptations resulted in the emergence of interest associations characterised by low levels of generalisability and governability. These new associations co‐exist with neo‐corporatist ones, rendering the overall training system surprisingly heterogeneous.